Phosphorus kinetics in tissues of young Santa Ines sheep - Louvandini H.; Vitti D.M.S.S.; Bueno I.C.S.; Portilho F.P.; McManus C.M. (Nutritional and foraging ecology of sheep and goats, 2009)
Santa Ines is one of the most popular hair sheep breeds from Brazil used for meat production. This study was carried out to determinate the effect of phosphorus (P) intake on the P kinetics in tissues. Twelve Santa Ines sheep (20 weeks old and live weight 22.6 ± 2.21 kg), were housed in metabolism cages and fed 600 g/animal/day of Coast cross hay and concentrate mixture (200 g/animal/day of cassava flour and 15 g/animal/day of urea) with daily supplements of dicalcium phosphate (0, 1.5, 3.0 and 4.5 g P/animal). A group of 3 animals received each level of dicalcium phosphate and after 22 days they were given a 0.5 ml saline solution with an intravenous dose of 7.4 MBq 32P to trace the P kinetics in tissues. Blood was collected for the subsequent seven days and radioactivity decay measured. Animals were slaughtered and samples from bone, liver, kidney, heart and muscle were taken. The concentration of P, biological half-life, retention, standardized activity [(activity in tissue/(mg P/g tissue))/(activity injected/live weight)] and relative activity (activity in tissue/activity in plasma) of 32P were evaluated in relation to P intake and analysed by regression analysis. No significant relationship was observed on stable P concentration in tissues and P intake. Biological half-life, retention (liver, kidney and heart) and standardized activity (liver, kidney and heart) of 32P were found to have a negative linear relationship with P intake. There was a positive linear relationship between relative activity (bone, kidney and heart) and P consumed. It was concluded that dietetic P influences the turnover of P in tissues of young Santa Ines sheep.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)